Labour Supply during Lockdown and a "New Normal": The Case of the Netherlands - Hans-Martin von Gaudecker; Radost Holler; Lena Janys; Bettina M. Siflinger; Christian Zimpelmann (Institute of Labor Economics (IZA), 2020)
We document the evolution of hours of work using monthly data from February to June 2020. During this period, the Netherlands experienced a quick spread of the SARS-CoV-2 virus, enacted a lockdown for a period of six weeks and gradually opened thereafter. We show that during lock-down, substitutability between work from home and at the workplace or essential worker status are key to maintain a large fraction of pre-crisis hours of work. These pandemic-specific mechanisms become much less important as social distancing restrictions are eased in May and June. Labor supply recovers quickly in sectors affected heavily during lockdown, but goes down in other areas of the economy. The latter is unlikely caused by pandemic-induced supply changes; diminished demand is a more plausible explanation. Analyzing take-up of economic support programs, we find suggestive evidence that wage subsidies and other programs helped limit the early-stage impact of the crisis along the extensive margin.
Keywords: J2; H3; 330; hours of work; telecommuting; essential workers; labor hoarding; COVID-19